PEMANFAATAN MEDIA SOSIAL DALAM PEMASARAN PRODUK UMKM DI DESA LUKSAGU, KABUPATEN BANGGAI KEPULAUAN - Hadiyati, Rini; Belani, Sriwanti (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2023)
This research discusses how the use of social media in marketing UMKM products in Luksagu Village, Tinangkung Utara District, Banggai Kepulauan Regency. The research objective is to introduce UMKM products to the wider community in order to get a bigger market potential. This research method is qualitative by using phenomenological approach. The research result is, the use of social media provides good prospects for increasing the sales of UMKM products in Luksagu Village, Tinangkung Utara District, Banggai Kepulauan Regency which is experiencing the impact of the COVID-19 pandemic. This is because the digital marketing system provides an online buying and selling platform, in order to facilitate the ordering and purchasing process. So that buyers can interact with UMKM owners to make transactions directly